Determinant of Firm Value in Property, Real Estate and Construction Sector 2015-2017 - Sari, Ririn Amelia; Ardiansari, Anindya (Management Analysis Journal, 2019)
This study aims to find empirical evidence of the effect of capital structure, institutional ownership and financial performance on firm value. The population in this study are service companies in the property, real estate and building construction sectors listed on the Indonesia Stock Exchange in 2015-2017. The total population of this study was 79 companies. After using a purposive sampling technique, the number of samples became 58 companies. Firm value is proxy with Price to Book Value (PBV), capital structure is proxy with Debt to Equity Ratio (DER), institutional ownership is proxy with the percentage of institutional shares, and financial performance with Return on Equity (ROE) and Return on Assets (ROA). Data sources are from the Indonesia Stock Exchange (IDX) and the Indonesian Capital Market Directory (ICMD). Data processing using Eviews 9. The analysis technique used in this study is panel data regression. The results of this research show that financial performance with ROE proxy has a significant positive effect on firm value while capital structure, institutional ownership, and ROA do not affect on firm value in the Property, Real Estate, and Building Construction sectors listed on the Indonesia Stock Exchange in 2015-2017.